Evaluation of Morphologic and Morphometric Characteristics of the Mental Foramen and Anterior Loop in a Turkish Subpopulation Using Cone Beam Computed Tomography - Doğan, Fatma Büşra; Akgünlü, Faruk (Journal of Dentistry Indonesia, 2023)
Objective: Before a surgical intervention in the mandibular interforaminal area, it is important to have a full understanding of the anatomy of the mandibular anterior segment. The evaluation of anatomical structures, variations and pathologies is performed with radiological imaging methods. Today, cone beam computed tomography (CBCT) is an imaging method which offers all the features necessary for this. In addition to its importance in surgical applications, it is also valuable in terms of anatomical studies thanks to the reliability of its measurements and the fact that it allows for a three-dimensional evaluation. The mental foramen and anterior loop are some of the most significant anatomical structures in the lower jaw. The aim of this study was to determine the characteristics of mental foramen according to age and gender in a Turkish population and to evaluate anterior loop length and the frequency of anterior loop. Methods: In this retrospective study, CBCT images from 148 patients (89 females and 59 males) were examined. Images of the mental foramen and interforaminal area of patients who were over 18 years of age were included in the study, while images with mandibular pathology and without occlusal closure to at least premolar teeth were excluded. Linear measurements of the mental foramen were repeated three weeks later by the same observer. Descriptive statistics (mean, standard deviation) and the Kolmogorov-Smirnov, Kruskal-Wallis, Mann-Whitney U, ANOVA tests and the t-test were used to evaluate the data. Results: The morphological and morphometric features of the mental foramen, which is a characteristic structure in mandibular bone, were determined. No statistically significant difference was found between the age groups in the morphometric characteristics of the mental foramen, but a statistically significant difference was found according to gender. The most frequently detected oval shape and P3, and P4 positions were similar to the other studies conducted in Turkish populations. The prevalence of anterior loop was 58%. Conclusion: Detailed preliminary analysis focusing on anesthesia and surgical interventions is important in order to avoid possible complications.